Child migration for work - Khair, Sumaiya; Refugee and Migratory Movements Research Unit. (Dhaka : Refugee and Migratory Movements Research Unit, 2008)
Predominantly on socio-economic conditions of child labor in Bangladesh.
"Development Research Centre on Migration, Globalisation, and Poverty".
Includes bibliographical references (pages 116-119).
Keywords: Child labor -- Bangladesh -- Social conditions; Child labor -- Bangladesh -- Economic conditions; Migration, Internal -- Bangladesh